Green Bonds, Environmental, Social, and Governance Scores, and the Greenwashing Puzzle: Insights from the ASEAN Region - Viona, Crecia; Anrika, Esthervany; Dewi, Camilla Tiara; Fauzi, Fitriya (International Journal of Energy Economics and Policy, 2025)
This study examines the relationship between green bond issuance and the achievement of sustainability goals within the framework of corporate social responsibility (CSR) in the ASEAN region. With the increasing attention to environmental and social responsibility, where green bonds play as a strategic financial instrument, it is important to evaluate the effectiveness of green bonds in encouraging sustainability practices and identify potential greenwashing practices in the region. Covering the six ASEAN countries, namely Indonesia, Singapore, Malaysia, Thailand, Vietnam, and the Philippines, this study uses random-effect GLS regression and logistics results over the period 2019-2023. The result shows that green bond issuance helps increase the ESG score indirectly through the green financing project. With this, we also uncovered that a higher ESG score but a lower carbon emissions score does not define the probability of greenwashing itself. Higher ESG scores are proven to lower the probability of greenwashing, while the emissions score has no significant impact on the probability of greenwashing. Overall, this indicates that green bond issuance really does help increase ESG score, making it a great strategic tool for both the environment and the firm’s green financing. With this, we can rely on the ESG score to identify greenwashing practices for firms that issue green bonds, as the higher the ESG score, the lower the probability of greenwashing practices.